2018
DOI: 10.1186/s12929-018-0430-8
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2-mediated cancer progression and therapeutic resistance in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a head and neck cancer with poor clinical outcomes and insufficient treatments in Southeast Asian populations. Although concurrent chemoradiotherapy has improved recovery rates of patients, poor overall survival and low efficacy are still critical problems. To improve the therapeutic efficacy, we focused on a tumor-associated protein called Annexin A2 (ANXA2). This review summarizes the mechanisms by which ANXA2 promotes cancer progression (e.g., proliferation, migration, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 112 publications
(93 reference statements)
0
61
0
Order By: Relevance
“…Anxa2 overexpression promotes chemoresistance in non-small cell lung cancer, pancreatic cancer, neuroblastoma, and hepatocarcinoma [16,17,54,55]. Moreover, Anxa2 confers increased invasiveness in breast cancer (Additional file 2: Figure S5 B and C) [18,56,57]; Anxa2 knockdown also inhibits migration and invasion in nasopharyngeal carcinoma [21,22]. However, whether Anxa2 expression per se or its phosphorylated form confers the aggressive phenotype of drug-resistant cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxa2 overexpression promotes chemoresistance in non-small cell lung cancer, pancreatic cancer, neuroblastoma, and hepatocarcinoma [16,17,54,55]. Moreover, Anxa2 confers increased invasiveness in breast cancer (Additional file 2: Figure S5 B and C) [18,56,57]; Anxa2 knockdown also inhibits migration and invasion in nasopharyngeal carcinoma [21,22]. However, whether Anxa2 expression per se or its phosphorylated form confers the aggressive phenotype of drug-resistant cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of Anxa2 in these cells not only confers resistance to anticancer agents, but also enhances their aggressive behavior [18,21,22]. Moreover, clinical studies have shown that Anxa2 overexpression is positively correlated to poor response to anticancer agents and rapid recurrence in cancer patients who had received chemotherapy [21,[23][24][25]. This evidence suggests that Anxa2 is a key protein that links drug resistance and cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…gov/pubmed/) (Table II). In comparison with the genetic and proteomic data previously published for adenomyosis and (13,30), L-selectin ligand (31) and Annexin A2 (ANXA2) (32)(33)(34)(35), were considered to be target genes for adenomyosis. These previous studies revealed that, among these, 4 genes (IGF1, KISS1, NCAM1 and ANXA2) were upregulated, and 3 genes (OPN, VCAN and L-selectin ligand) were downregulated.…”
Section: Differentially Expressed Genes and Their Functions Between Amentioning
confidence: 99%
“…i) ANXA2. ANXA2 acts as a tumor-associated protein and promotes cancer proliferation, invasion, EMT and metastasis (35). ANXA2 expression has been found to be upregulated (32) and downregulated (33,34) in adenomyosis and endometriosis, respectively.…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%